Rural tourism development through the role of village government: Study of Purbayan Tourist Village, Indonesia - Agung Sulistyo; Tri Eko Yudiandri; Fitri Dwi Kusumawati; Dwi Agus Kristianto; Musadad Musadad (Borneo Novelty Publishing, 2025)
Purpose – This study examine to examine the role of village government in developing regional potential, particularly in rural tourism.Methodology/Design/Approach – This qualitative case study investigates how the village government develops the Purbayan Tourism Village through planned work programs. Data were collected via semi-structured interviews with selected stakeholders.Findings – The village government plays a key role in developing the Purbayan Tourism Village, acting as a driver in optimizing rural tourism potential. Programs emphasize sustainability through community deliberation, legal strengthening, external collaboration, and management innovation. Policies are responsive to local needs while aligned with regulations.Originality/Value – This study highlights village government policies that contribute to sustainable tourism development.